Nodular Posterior Scleritis Mimicking Choroidal Tumor in a Patient With Systemic Lupus Erythematous: A Case Report and Literature Review. Issue 5 (September 2016) - Sin, Pui Yee; Liu, David Ta Li; Young, Alvin L.
Abstract : Purpose: Posterior scleritis is a potentially blinding ocular disorder that is often difficult to diagnose because of the low incidence and varied clinical presentation. Nodular posterior scleritis can mimic a choroidal mass and pose diagnostic difficulties to clinicians. This case report and literature review aimed to evaluate the clinical presentation of nodular posterior scleritis that mimics choroidal tumor, along with the etiologies, treatment modalities, and outcomes. Design: Case report and literature review. Methods: We describe a case of nodular posterior scleritis that presented as a choroidal mass in a patient with systemic lupus erythematous. Previous reports on nodular posterior scleritis presenting as choroidal mass were reviewed. Results: Including this case, there were 14 cases of nodular posterior scleritis presenting as a choroidal mass in the past 20 years. The mean age was 50 years, with women being predominant (79%). All cases had unilateral eye involvement. Most patients presented with a drop in vision (ranging from counting fingers to visual acuity of 20/30). The cause was mostly idiopathic in 79% of reported cases. Most patients (71%) were treated with a course of systemic steroids. Two patients required systemic steroids together with immunosuppressive agents. Most patients responded to treatment with visual recovery and resolution of the choroidal mass. Conclusions: Nodular posterior scleritis is a rare disease that can easily be confused with choroidal tumor. Associated ocular pain is a useful feature for differentiating nodular posterior scleritis from other forms of choroidal masses. Early diagnosis and prompt treatment usually can deliver a good outcome.